(untitled) (Actual Problems of Mind, 2023)
Decision-making is one of the main structural components of social interaction. When asked to justify a decision in question, the usual response is to construct arguments. They establish preferences between alternative actions. Such arguments rely on preferences between values. Preferences between values, in turn, are established by evaluating them, and assigning them the degrees of importance for decision-making. In this way, the evaluated values are included in the decision-making justification process. The success of the justification of the decision depends, to a large extent, on the transmitting of the evaluated value to the person to whom such justification is addressed. When decision-making is emotional, values gain degrees of importance through emotional evaluation. And the perception of the justification of the decision can also be emotional. An emotional reaction to it is an evaluative reaction. It shows whether the transmitting of value is successful, whether the value is accepted and, in the result, whether the proposed justification for the decision is accepted or not. The question is how arise the emotional evaluations that determine preferences between values. It is proposed to consider emotional evaluation as the result of an intuitive inference – emotional evaluation induction. Making an inference is a consequence of perceiving an expression of emotion, a reaction to an emotional expression of an evaluative attitude to value. Emotional inferences are plausible inferences. Their conclusions are potentially cancellable. Usually, the reasons for cancelling the conclusion of an argument supporting a decision are inconsistency or incompleteness of information. The dynamics of emotional states is added to these reasons. Transmitted and accepted values lead to the emergence of collective intentionality which, apart from everything else, arises due to a series of inferences, which, to some extent, are «guided» by emotions.